2005
DOI: 10.1002/qre.734
|View full text |Cite
|
Sign up to set email alerts
|

Process Improvement in the Microelectronic Industry by State Space Modelling

Abstract: The exponentially weighted moving average (EWMA) model can be applied to a process controlling the thickness of nitride layers in the manufacture of microelectronic devices, involving the standard use of the notions of EWMA control chart, EWMA full adjustment and EWMA deadband adjustment charts for process monitoring and process improvement. We suggest that a dynamic step forward to process improvement is gained by considering basic state space models, which are known as local-level models. The EWMA predictor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…First we fit a local level model to the multivariate process and then we apply a univariate modified EWMA control chart to the logarithm of the Bayes' factor to monitor the dispersion of the predictive distribution of the data from the target distribution. Our model makes use of a generalization of the Shewhart-Deming model for multivariate autocorrelated processes (Deming 29 , del Castilo 3 , Triantafyllopoulos et al 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…First we fit a local level model to the multivariate process and then we apply a univariate modified EWMA control chart to the logarithm of the Bayes' factor to monitor the dispersion of the predictive distribution of the data from the target distribution. Our model makes use of a generalization of the Shewhart-Deming model for multivariate autocorrelated processes (Deming 29 , del Castilo 3 , Triantafyllopoulos et al 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed methodology is a semi-conjugate Bayesian procedure and, although it involves a simulation step, it is found to be fast and accurate. The predictions produced outperform the relevant predictions of Box and Lucen˜o [4,5] and Triantafyllopoulos et al [18] returning notably lower sum of squared errors. The benefit gained from the entire distribution of the NVR is a step forward in the development of the local level model with theoretical and practical advantages.…”
Section: Introductionmentioning
confidence: 48%
“…40 or 60 time points), it seems that the Bayesian paradigm is the appropriate approach to be considered, since with the inclusion of prior information, this can lead to more accurate predictions [15]. Triantafyllopoulos et al [18] adopt a local level predictor for feedback adjustment and these authors show that the noise variance ratio (NVR) plays an important role in control. In the above paper it is shown that by manually changing the NVR a much improved adjusted process can be achieved with much lower sum of squared errors than in the usual EWMA.…”
Section: Introductionmentioning
confidence: 98%
“…Without accurate and timely forecasts, planning, scheduling, and procurement decisions can be seriously in error, leading to waste and inefficiency throughout the supply chain. Triantafyllopoulos et al 6 provided an excellent example of how time series analysis methods were used in improving performance in the microelectronics industry.Finally, a reminder to readers that Quality and Reliability Engineering International 2005; 21(3):221-328 was a special issue devoted to Six Sigma that explored many ideas useful for extending, strengthening, and expanding its applications. Many of the articles in that special issue are useful reading to accompany the article by Tang et al 1 .…”
mentioning
confidence: 99%
“…Without accurate and timely forecasts, planning, scheduling, and procurement decisions can be seriously in error, leading to waste and inefficiency throughout the supply chain. Triantafyllopoulos et al 6 provided an excellent example of how time series analysis methods were used in improving performance in the microelectronics industry.…”
mentioning
confidence: 99%